Internalizing the Exemplary Value of Brigadier General KH Syam'un for the Modern Generation - Nurdina Fitri; Siti Muamala; Encep Syarifudin; Machdum Bachtiar (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
In The Current Era Of Digital Globalization, The Modern Young Generation Is Faced With A Crisis Of Role Models Who Are Able To Balance Aspects Of Spirituality And Professionalism Discipline, So It Is Necessary To Internalize Or Re-Instill The Figure Of A Historical Figure Who Has A Multi-Talented Character To Be A Moral Compass For The Current Generation Z. The Purpose Of This Article Is To Analyze The Internalization Of The Exemplary Character Of Brigadier General KH Syam'un A Hero From Banten In The Modern Generation, The Importance Of This Research To Answer The Challenges Of Modern Education In Shaping The Character Of The Young Generation To Become Future Leaders Who Have Character And Islamic Values, This Research Method Uses A Historical-Qualitative Approach, With Data Collection Techniques And Literature Studies. The Results Of This Finding Are That The Figure Of KH Syam'un Can Be A Source Of Transformative Learning That Not Only Enriches The Character Dimensions Of The Modern Generation, But Also Strengthens The Orientation Of Education Towards Quality And Relevance In The Era Of Disruption.